Effects of fermented Arctium lappa L. root by Lactobacillus casei on hyperlipidemic mice - Chen, MingJu; Wu, Yuxiao; Yang, Hongxuan; Liu, Tianfeng; Han, Tongkun; Dai, Wangqiang; Cen, Junyue; Ouyang, Fan; Chen, Jingjing; Liu, Jianxin; Zhou, Lin; Hu, Xuguang (Frontiers in Pharmacology, 2024)
This study aimed to establish a fermentation system based on Lactobacillus casei (LC) and Arctium lappa L. root (AR), elucidate differences in metabolites' pre-and post-fermentation using untargeted metabolomics, and assess the impact of LC-AR on gut microbiota in high fat diet-induced hyperlipidemic mice. Compared to AR, LC-AR exhibited stronger in vitro antioxidant activity and higher levels of metabolites. Moreover, it demonstrated improved liver injury as well as better regulation of lipid levels, pro-inflammatory cytokine levels, and cholesterol-related mRNA. According to the 16S rRNA analysis, LC-AR reduced the relative abundance of Firmicutes/Bacteroidetes at the phylum level, which was significantly negatively correlated with triglycerides, total cholesterol, and low-density lipoprotein cholesterol levels. Thus, LC-AR has promising potential as functional food and drug raw materials in improving hyperlipidemia.Hyperlipidemia is a metabolic illness characterized by excessive lipid levels and is a key risk factor for stroke and cardiovascular diseases (Crea et al., 2023;Alloubani et al., 2021;Stewart et al., 2020) Multiple clinical studies have proved that statins and fibrates exhibit good performance in